Meta-skills-oriented academic management in higher education: evidence from Chinese HEIs - Chi Che; Sukanya Chaemchoy; Pruet Siribanpitak (International Journal of Evaluation and Research in Education (IJERE), 2026)
Higher education institutions (HEIs) increasingly face pressure to develop graduates’ meta-skills, yet meta-skills are typically treated as learner-level outcomes rather than an institutional management orientation that can reshape academic management systems. This study proposes and tests a meta-skills-oriented academic management framework that links meta-skills orientation (metacognitive capacity, emotional intelligence, and motivational competence) to academic management frames (structural, human resource, political, and symbolic) and institutional performance. Using a cross-sectional survey of 2,406 academic administrators and faculty from 60 Chinese HEIs (national key, provincial, and regular colleges) selected through stratified sampling, the study employed validated questionnaire measures and analyzed data via structural equation modeling (SEM) (AMOS 26.0). The model demonstrated acceptable fit (CFI=0.968; RMSEA=0.042). Meta-skills orientation positively predicted structural (β=0.685), human resource (β=0.573), political (β=0.412), and symbolic (β=0.524) frames (all p<0.001), while structural (β=0.486) and human resource (β=0.445) frames significantly predicted institutional performance (all p<0.001). Multi-group analysis indicated stronger meta-skills-to-structural pathways in national key universities than other HEI types. The findings position meta-skills orientation as an actionable institutional logic and provide frame-specific levers for evidence-based academic management reform.